Gamifying Science Education: How Wordwall-Integrated Joyful Learning Enhances Cognitive Outcomes and ARCS Motivation in Elementary School - Shomayya Rachmawati; Iis Rachmawati; Silvia Ernawati; Sintha Wahjusaputri (Jurnal Penelitian Ilmu Pendidikan, 2026)
Teacher‑centered instruction in elementary science often fails to engage students, limiting learning outcomes and motivation. Gamification tools like Wordwall offer promise, yet evidence for their integration within joyful learning—especially under Indonesia’s Merdeka Curriculum—remains scarce. This quasi‑experimental study evaluated the effectiveness of Wordwall‑based joyful learning on sixth‑graders’ cognitive outcomes and motivation in Natural and Social Sciences (IPAS), while quantifying effect sizes. A nonequivalent control group design was used (experimental n = 30, control n = 30). The experimental group received four sessions of Wordwall games (Match Up, Maze Chase, Airplane); the control group had conventional instruction. Learning outcomes were measured with a 20‑item test (KR‑20 = 0.82); motivation with an ARCS questionnaire (Cronbach’s a = 0.85). Analysis included N‑Gain, independent t‑tests, and Cohen’s d. The experimental group showed significantly higher improvement (N‑Gain = 0.68 vs. control 0.35; Cohen’s d = 1.58, 95% CI [0.98,2.18], p < 0.001). Motivation scores increased by 25.7 points (experimental) vs. 7.3 points (control); Cohen’s d = 1.42, p < 0.001. The largest gains occurred in the Attention and Satisfaction subscales of the ARCS model. Wordwall‑based joyful learning substantially enhances both cognitive outcomes and learning motivation in elementary IPAS education. These findings provide empirical support for gamified, student‑centered approaches under the Merdeka Curriculum. Future research should explore long‑term retention and cross‑context replication.